Vitamin D attenuates biofilm-associated infections via immunomodulation and cathelicidin expression: a narrative review. Issue 1 (2nd January 2023) - Benson, Ruby; Unnikrishnan, Mazhuvancherry Kesavan; Kurian, Shilia Jacob; Velladath, Saleena Ummer; Rodrigues, Gabriel Sunil; Chandrashekar Hariharapura, Raghu; Muraleedharan, Anju; Bangalore Venkateshiah, Dinesh; Banerjee, Barnini; Mukhopadhyay, Chiranjay; Johnson, Aieshel Serafin; Munisamy, Murali; et al.
ABSTRACT: Introduction: Infections are becoming more difficult to treat, at least partly on account of microbes that produce biofilms. Reports suggest that decreased levels of antimicrobial peptides like cathelicidin, elevated levels of inflammatory cytokines, and biofilm formation are all associated with vitamin D deficiency, making vitamin D – deficient individuals more susceptible to infection. Infections attributable to biofilm-producing microbes can be managed by adjuvant therapy with vitamin D because of its immunomodulatory role, particularly because of the ability of vitamin D-pathway to induce the antimicrobial peptides like cathelicidin and decrease proinflammatory cytokines. Areas covered: This narrative review covers biofilm formation, infections associated with biofilm due to vitamin D deficiency, putative role of vitamin D in host protection and the effect of vitamin D supplementation in biofilm-associated infections. A comprehensive literature search in PubMed and Google Scholar utilizing suitable keywords at multiple time points extracted relevant articles Expert Opinion: Although vitamin D deficiency has been associated with infections by biofilm producing microbes, comprehensive clinical trials in various ethnicities are required to understand the likely relationships between vitamin D receptor gene expression, cathelicidin levels, and infection outcome. Current evidence hypothesizes that maintaining normal vitamin D level can help prevent and treat these infections.